Effects of Jianpi Bushen Therapy for Treatment of CKD Anemia: A Meta-Analysis of Randomized Controlled Trials - Li, Liang; Li, Chengyin; Zhou, Yu; Xu, Qi; Wang, Zilin; Zhu, Xiaoyun; Ba, Yuanming (Frontiers in Pharmacology, 2020)
Objectives To evaluate the efficacy of Traditional Chinese Medicine, specifically Jianpi Bushen (JPBS) therapy, for treatment of patients with chronic kidney disease (CKD) anemia. Methods Randomized controlled trials of JPBS therapy for CKD anemia were searched and selected from seven electronic databases. The Cochrane collaboration tool was used to conduct methodological quality assessment. RevMan v5.3 software was utilized to perform data analysis. Results In total, 12 randomized controlled trials with 799 patients met the meta-analysis criteria. The aggregated results indicated that JPBS therapy is beneficial for CKD anemia by improving the clinical efficacy rate [risk ratio (RR) = 1.23, 95% confidence interval (CI): (1.14, 1.33), P < 0.00001] and hemoglobin (Hb) [weighted mean difference (WMD) = 9.55, 95% CI: (7.97, 11.14), P < 0.00001], serum ferritin (SF) [WMD = 6.22, 95% CI: (2.65, 9.79), P = 0.0006], red blood cell (RBC) [WMD = 0.31, 95% CI: (0.24, 0.38), P < 0.00001], hematocrit (HCT) [WMD = 2.95, 95% CI: (2.36, 3.54), P < 0.00001], serum creatinine (SCr) [WMD = 64.57, 95% CI: (33.51, 95.64), P < 0.0001], and blood urea nitrogen (BUN) levels [WMD = 3.76, 95% CI: (2.21, 5.31), P <0.00001]. Furthermore, evidence suggests that JPBS therapy is safe and does not increase adverse reactions compared with western medicine (WM) alone. Conclusion This study found that JPBS therapy has a positive effect on the treatment of CKD anemia. However, more well-designed, double-blind, large-scale randomized controlled trials are needed to assess the efficacy of JPBS therapy in the treatment of CKD anemic patients.